Antosha and Levitasha : the shared lives and art of Anton Chekhov and Isaac Levitan - Gregory, Serge Vladimir, 1948- (Northern Illinois University Press, 2015)
"Antosha and Levitasha is the first book in English devoted to the complex relationship between Anton Chekhov and Isaac Levitan, one of Russia's greatest landscape painters. Outside of Russia, a general lack of familiarity with Levitan's life and art has undermined an appreciation of the cultural significance of his friendship with Chekhov. Serge Gregory's highly readable study attempts to fill that gap for Western readers by examining a friendship that may have vacillated between periods of affection and animosity, but always reflected an unwavering shared aesthetic. In Russia, where entire rooms of galleries in Moscow and St. Petersburg are devoted to Levitan's paintings, the lives of the famous writer and the equally famous artist have long been tied together. To those familiar with the work of both men, it is evident that Levitan's "landscapes of mood" have much in common with the way that Chekhov's characters perceive nature as a reflection of their emotional state. Gregory focuses on three overarching themes: the artists' similar approach to depicting landscape; their romantic and social rivalries within their circle of friends, which included many of Moscow's leading cultural figures; and the influence of Levitan's personal life on Chekhov's stories and plays. He emphasizes the facts of Levitan's life and his place in late nineteenth-century Russian art, particularly with respect to his dual loyalties to the competing Itinerant and World of Art movements. Accessible and engaging, Antosha and Levitasha will appeal to scholars and general readers interested in art history, late nineteenth-century Russian culture, and biographies"--